Seasonal Characteristics of Mesoscale Coupling between the Sea Surface Temperature and Wind Speed in the South China Sea - Sun, Shuangwen; Fang, Yue; Zu, Yongcan; Liu, Baochao; Tana, -; Samah, Azizan Abu (American Meteorological Society, 2020)
The seasonal characteristics of the mesoscale coupling between sea surface temperature (SST) and wind speed in the South China Sea (SCS) are investigated using satellite observations. The correlation between mesoscale SST and wind speed is highest in winter. The region of high correlation is located in the central SCS in the early stage of the winter monsoon. It then gradually shifts northward in the following months and is located in the northern SCS in the late stage of the winter monsoon. In summer, the region of high correlation is located to the east of the Vietnam coast. Two controlling factors are crucial in mesoscale SST-wind speed coupling: the mesoscale SST gradient and the wind speed steadiness. The mesoscale SST gradient is fundamental in mesoscale coupling, but a steady wind speed also plays an important role. The development of significant coupling depends on the relative contribution of these two factors. For regions where the mesoscale SST gradient is relatively weak, a very steady wind field is required for detectable mesoscale coupling to occur, whereas in regions where the wind speed is less steady, a stronger mesoscale SST gradient must exist for coupling to develop. Variations in wind speed steadiness can well explain the inconsistency between the spatial patterns of the mesoscale SST gradient and the intensity of coupling. The wind speed steadiness is a good factor with which to evaluate the constraining effect of the background wind field variability on the development of mesoscale coupling in the SCS. © 2019 American Meteorological Society. For information regarding reuse of this content and general copyright information, consult the AMS Copyright Policy (www.ametsoc.org/PUBSReuseLicenses).